Shaw family papers - Shaw, Samuel, 1768-1827.; Shaw, Sally Campbell, 1769-1825.
Chiefly social invitations to events in Washington, D.C.; memoirs of Shaw's wife, Sally Campbell Shaw, describing visits with President James Monroe, his wife, Elizabeth Monroe, and Hannah Nicholson Gallatin and giving details of furnishings and fashion; and proclamation (1815 January 1) signed by James Madison and James Monroe appointing Samuel Shaw as hospital surgeon, U.S. Army.
U.S. representative from Vermont and army surgeon.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Gallatin, Hannah Nicholson, -- -1849.; Madison, James, -- 1751-1836.; Monroe, Elizabeth, -- 1768-1830.; Monroe, James, -- 1758-1831.; United States. -- Army -- Surgeons; Fashion -- United States -- 19th century; House furnishings -- United States -- 19th century; Washington (D.C.) -- Social life and customs; Physicians; Representative, U.S. Congress -- Vermont